Molecular variability of Fusarium oxysporum f. sp. lini isolates by RAPD analysis: MOLECULAR VARIABILITY OF FUSARIUM OXYSPORUM F. SP. LINI ISOLATES BY RAPD ANALYSIS - MOHD AKRAM; P K SINGH; JYOTI SINGH; R L SRIVASTAVA (Journal of Oilseeds Research, 2014)
Seven isolates of Fusarium oxysporum f. sp. lini collected from different linseed growing areas in India were analyzed by random amplified polymorphic DNA-polymerase chain reaction. Two isolates (FOL 1 and FOL 2) found non-pathogenic to linseed crop. Twenty random decamer primers were used for amplification. All the primers revealed scorable polymorphism among the isolates and a total of 156 bands were recorded. Amplification patterns of non-pathogenic Fusarium isolates were entirely distinct from those of pathogenic isolates. Seventeen primers generated isolate specific bands which would be highly useful in the identification and characterization of Fusarium isolates. RAPD markers showed substantial genetic diversity among the different isolates with maximum of 0.89 between FOL1 and FOL6. UPGMA cluster analysis was used to generate a dendogram showing relationship between them. Isolates were clustered in to three groups corresponding to their genetic similarity and physiological reactions. RAPD markers can be quick and reliable alternative for differentiating isolates of Fusarium oxysporum f. sp. lini in to different groups.